2009
DOI: 10.1007/s00436-009-1585-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression in Spirometra erinacei according to its development in its final host

Abstract: This study was undertaken to identify genes involved in the growth and development of Spirometra erinacei larvae, an intestinal tapeworm of cats and dogs, within the final host. The differential protein expression at three different stages of S. erinacei, the plerocercoid larvae, 8-day-old juveniles, and adults, was compared using two-dimensional electrophoresis. Specifically or highly expressed proteins in juvenile worms were analyzed by matrix-assisted laser desorption/ionization time-of-flight mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the paper by Kim et al ( 2009 ), differential protein expression of three different stages of S. erinacei (plerocercoid metacestode, pre-strobilated juveniles, and adults) was compared. They observed differences in expression of energy-metabolism enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the paper by Kim et al ( 2009 ), differential protein expression of three different stages of S. erinacei (plerocercoid metacestode, pre-strobilated juveniles, and adults) was compared. They observed differences in expression of energy-metabolism enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The other identified proteins are involved in a wide range of biological functions. Kim et al ( 2009 ) observed that thioredoxin family proteins are highly expressed only in pre-strobilated juvenile worms of S. erinacei . This protein plays important roles in protection from reactive oxygen species produced by host inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ES antigens of living plerocercoids can induce a strong humoral response involving the generation of specific antibodies and may be very important for serodiagnosis as they are easily targeted by the immune system. In addition, the antigenic composition of sparganum from different hosts (snakes or mice) were different (Yang 2004), and the differential proteins were expressed at different development stages in its host (Kim et al 2009). Hence, we firstly inoculated into mice with spargana collected from wild frogs, then prepared the ES antigens with the spargana recovered from the infected mice.…”
Section: Discussionmentioning
confidence: 99%